IMPLEMENTASI MANAJEMEN PENDIDIKAN SEKOLAH BERBASIS BOARDING DALAM MENINGKATKAN MUTU PENDIDIKAN DI AL-WILDAN ISLAMIC BOARDING SCHOOL TANGERANG - Fitria, Rizka (Management of Education: Jurnal Manajemen Pendidikan Islam, 2021)
This study wanted to describe school management during completion and completion at Al Wildan Islamic Boarding School. This type of qualitative research with descriptive methods. The research objects are the Principal and Director of Education, the curriculum section, the personnel section, the infrastructure section, the student body section, the public relations section, the finance section, and the administration section. Researchers used methods of observation, interviews, and documentation. Data data in the form of data data. The method of data analysis includes 14 activities: first, data collection and data reduction, Second, data in the form of narrative. Third, the withdrawal of conclusions. The results of the research shown Al Wildan boarding school has not been put to good use. The integration is seen in activity programs and learning programs. Management here is categorized into 7 types namely: curriculum management, personnel, students, infrastructure, finance, public relations, and special services. So, between the management in the school and in boarding are interrelated. Furthermore, according to the results of a study done at Tangerang Al Wildan Islamic Boarding School using TQM techniques. The TQM that has been implemented is running well. This is evidenced through an explanation of the terms of the TQM implementation that has been included. As a commitment of the principal, have the vision, mission, and goals of the school, benefit from its success, have published influence, and a board of directors.